Predictors of risk-taking behavior trends among racial minority adolescents: Examining interactive effects using latent growth analysis - Henry, Una Y. (Kansas State University, 2020)
Risk-taking behavior (RTB) among juveniles has grown steadily since the first juvenile justice system was established. This study examines the relationship between future expectations of racial minority adolescents and their RTB across seven years. The role of multiracial identity and the malleability of this identity in RTBs were further examined, as were differences across sexes. Data from Waves 1 through 3 of the National Longitudinal Study of Adolescent Health (N = 1770; 796 males and 974 females) was utilized for this study. All participants indicated a minority race at Wave 1. Slightly more than 40% of the males and almost 60% of the females changed their race from Wave 1 to Wave 3. Latent growth curve modeling results not only suggest that although adolescents took fewer risk initially, adolescents who had significantly higher future expectations actually increased their RTB over time as compared to those with lower future expectations. While previous research has indicated that higher future expectations are associated with lower risk-taking behavior, the findings of this study suggest that higher future expectations is associated with an increase in risk-taking behavior over time. Shame and guilt and their ties to reflected appraisal and identity formation may be one way to understand this phenomenon. The higher one’s future expectations, likely the more positive their reflected appraisals and lower the anticipated shame. The more secure on is in their identity, the less likely that anticipated shame or guilt might influence their actions, as these responses would be seen as exceptions rather than indicative of their identity. Examination across sexes found that the relationship between future expectations and RTB attenuated among females to the point of insignificance but remained significant for males over time. As for moderators, results suggest that the inverse relationship between future expectations and initial reports of RTB is weaker among multiracial adolescents who identify as one race. Further, racial identity malleability moderated the initial relationship between future expectations and RTB in males but not females. Among racial minority males, racial identity malleability reverses the positive effect of future expectations on RTB. Last, racial identity malleability moderated the relationship between future expectations and the trend in RTBs in females but not males. It appears that racial minority adolescent females do not only have a less stable racial identity but the more flexible their racial identity, the more RTB despite having high future expectations. Clinical implications and further research are discussed.
Keywords: Adolescents; Juvenile delinquency; Multiracial; Racial identity; Future expectations